2014
DOI: 10.1007/s11904-014-0201-4
|View full text |Cite
|
Sign up to set email alerts
|

Changing Patterns of HIV Epidemic in 30 Years in East Asia

Abstract: The HIV epidemic in East Asia started relatively late compared to the rest of the world. All countries or areas, except for North Korea, had reported HIV and AIDS cases, with China being the major contributor to the epidemic. Though initially driven by injecting drug use in China, East Asia did not experience an explosive spread. Strong commitment in China and early harm reduction programs in Taiwan managed to reduce transmission substantially among injecting drug users. In contrast to China and Taiwan, inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 67 publications
0
37
1
1
Order By: Relevance
“…The countrywide scale-up of harm-reduction programs for persons who inject drugs and law enforcement campaigns on banning illegal plasma collection has significantly decreased and stabilized the HIV epidemic among both drug injectors and plasma donors (Shan et al, 2002; Suguimoto et al, 2014; Wu et al, 2007). In contrast, the proportion of new HIV cases due to sexual transmission increased from 33.1% in 2006 to 92.2% in 2014, during which male-to-male sexual transmission surged from 2.5% to 25.8% (Ministry of Health of the People's Republic of China AIDS Response Progress Report, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The countrywide scale-up of harm-reduction programs for persons who inject drugs and law enforcement campaigns on banning illegal plasma collection has significantly decreased and stabilized the HIV epidemic among both drug injectors and plasma donors (Shan et al, 2002; Suguimoto et al, 2014; Wu et al, 2007). In contrast, the proportion of new HIV cases due to sexual transmission increased from 33.1% in 2006 to 92.2% in 2014, during which male-to-male sexual transmission surged from 2.5% to 25.8% (Ministry of Health of the People's Republic of China AIDS Response Progress Report, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The spread of sexually transmitted diseases, especially HIV, is expected to rise in Japan, particularly among young adults 15. There is an established government scheme for free and anonymous testing and counseling for HIV, syphilis, Chlamydia , and gonorrhea at public health centers to improve access.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are a limited number of studies on the trends of invasive amebiasis in nonendemic countries 13. In Japan, invasive amebiasis is an emerging sexually transmitted parasitic disease, increasing alongside the incidence rates of other sexually transmitted infections (STIs) including human immunodeficiency virus (HIV), chlamydial, and gonococcal infections 14,15. Previous studies have indicated that HIV infection is a risk factor for invasive amebiasis 11,13,16,17.…”
Section: Introductionmentioning
confidence: 99%
“…HIV infection among men who have sex with men (MSM) is a serious public health threat, both locally and internationally [1][2][3][4][5]. In Hong Kong, the HIV prevalence increased alarmingly from 4.08% in 2011 [6] to 5.85% in 2014 [7].…”
Section: Introductionmentioning
confidence: 99%